Sirtuins as multifunctional regulators: Role in the pathogenesis of metabolic, inflammatory and neurodegenerative diseases and the effect of physical activity on their activity - Matuszyński, Wojciech; Matuszyńska, Maria; Nowicka, Patrycja; Jezierska, Karolina; Kalinowska, Weronika; Gural, Mateusz (Quality in Sport, 2025)
Sirtuins, a family of NAD+-dependent deacetylases and ADP-ribosyltransferases, regulate cellular homeostasis and adaptive responses to environmental changes. Comprising seven isoforms (SIRT1–SIRT7), these enzymes have diverse functions, including gene expression regulation, mitochondrial function, oxidative stress response, and cellular aging. Dysregulated sirtuin activity is implicated in metabolic, inflammatory, and neurodegenerative diseases such as obesity, type 2 diabetes, cardiovascular disease, Alzheimer’s, and Parkinson’s. Sirtuins modulate metabolic pathways by influencing glucose and lipid metabolism, enhancing insulin sensitivity, and promoting mitochondrial biogenesis. Their role in reducing inflammation and oxidative stress positions them as potential therapeutic targets for chronic conditions and age-related disorders. Compounds like resveratrol and lifestyle factors such as physical activity are potent sirtuin activators, highlighting their therapeutic potential. Physical activity, a cornerstone of non-pharmacological health interventions, increases NAD+ availability, upregulating sirtuin activity. This effect underscores exercise as a modulator of sirtuin pathways, with protective effects against chronic diseases. Studies show that regular physical activity can enhance sirtuin function, improving metabolic health, reducing oxidative damage, and providing neuroprotection. This review offers an overview of sirtuin biology, their role in disease pathogenesis, and the molecular mechanisms underlying the beneficial effects of exercise on sirtuin activity.